POPULASI BAKTERI DAN RESPIRASI MIKROBA TANAH PADA RHIZOSFER TANAMAN JAGUNG ( Zea mays L.) YANG DIBERI PUPUK TERPADU DAN BIOCHAR SEKAM PADI PADA MASA VEGETATIF MAKSIMUM - Saputra, Eta; Putu, Silawibawa; Susilowati, Lolita Endang; Dewi, Rika Andriati Sukma (AGROTEKSOS, 2023)
This study aims to determine the Bacterial Population and Microbial Respiration in the rhizosphere of corn plants due to the application of integrated fertilizers and rice husk biochar soil amendments during the maximum vegetative period. This research was conducted using an experimental method with polybag experiments in a greenhouse from July to September 2021. The experiment was arranged using a completely randomized design (CRD) with 7 treatment combinations P0 (control treatment), P1 (Urea + phonska administration), P2 ( Giving Urea + Phonska + Biochar), P3 (Giving Urea + Phonska + BPF), P4 (Giving Urea + Phonska + Biochar + BPF), P5 (Giving Urea + Phonska + BPF + Compost), P6 (Giving Urea + Phonska + Biochar) + BPF + Compost). Each treatment was repeated 3 times, so as many as 21 units of experimental polybags were obtained. Parameters measured were total bacterial population, population of phosphate solubilizing bacteria, soil microbial respiration, pH, cation exchange capacity, and C-Organic. The results showed that the application of integrated fertilizers (inorganic, compost and biological-BPF) and rice husk biochar had a significant effect. on the total bacterial population, BPF and soil microbial respiration in the corn plant rhizosphere observed at the maximum vegetative period. From this study, it was concluded that the combination of inorganic fertilizer + organic fertilizer + bpf and biochar was the best combination in increasing the total population of bacteria, phosphate solubilizing bacteria and soil microbial respiration.